A Volume-Stable Collagen Matrix (VCMX) to Treat Single Gingival Recessions Associated with Partially Restored Noncarious Cervical Lesions: A Case Series - Miguel, Manuela Maria Viana [UNESP]; Mathias-Santamaria, Ingrid Fernandes; Kopereck, Marina Strelow; Martins, Thiago Marchi; Nunes, Marcelo Pereira; Santamaria, Mauro Pedrine [UNESP] (Quintessence Publishing, 2025)
Collagen matrices have been developed as possible connective tissue graft substitutes to overcome patient discomfort, undesired palatal healing, and the limited amount of donor tissue. The aim of this case series is to assess a coronally advanced flap (CAF) with a volume-stable collagen matrix (VCMX) to treat single gingival recessions (GRs) associated with partially restored noncarious cervical lesions (NCCLs). Twelve patients diagnosed with single GRs (type 1; RT1) + NCCL (B+) were included in this study and received a restorative approach (partial composite resin with an apical margin 1 mm beyond the estimated cementoenamel junction [CEJ]) and a surgical approach (CAF+VCMX). Clinical and patient-centered assessments were recorded from 10 patients at baseline and 6 months postoperatively. Significant recession reduction (2.1 mm), clinical attachment level gain (1.34 mm), and combined defect coverage (51.67%) were observed at 6 months. The estimated root coverage was 69.48%, obtained using the estimated CEJ. No difference in keratinized tissue width was observed over time. A 0.42-mm gain in gingival thickness was observed after 6 months (P = .002) as well as an improvement in patient satisfaction due to better esthetics (P < .001). Within the present study’s limitations, CAF+VCMX provided a significant improvement in treating single GRs combined with a partially restored NCCL (B+).
Keywords: gingival recession; heterografts; tooth abrasion; tooth cervix